Metalanguage at Afro Brasil Museum: Bridges between curatorial work and art making - Ribeiro, Carla Brito Sousa (2021)
I propound that the collection exhibition of Afro Brasil Museum located in São Paulo, Brazil, features characteristics that well represent intersections between art creation and curatorial work, besides its dealt with institutional memory through less conventional exhibit designs. Thus, I seek a reflection about the interchange between curatorial work, art making and metalanguage arrangements within this museum. I introduce this exhibition as an institutional memorial – based on conversations and interviews with the museum staff, “absent dialogues” with its curator-director-artist and by the analysis of bibliographic material, so as the collection itself – due to my understanding of the exhibition as an imagery formed by composite images set by Emanoel Araújo. In order to communicate the singularity of this exhibition I bring a perspective of the objects exhibited, by means of the registers of fieldnotes and on, undertaking a dialogue with scholars from arts and humanities about curatorial work, the polysemy of image and the role of scenography. I discuss the art making of curatorial work and Emanoel Araújo’s métier as curator artist, supported by his concept A Mão Afro-Brasileira (The Afro-Brazilian Hand). In conclusion, I stress the relation textimage- public in order to communicate the singular aspects of its exhibition. Whilst the absence of consensus toward creativity and art agency while designing exhibitions, I assert that Araújo and his team strain the usual expectations on curatorial practice hence the limits of topographic arrangements and scenography schemes as a sensorial tool are extrapolated.